2012
DOI: 10.2119/molmed.2011.00277
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol Improves Impaired Hepatic Phosphatidylinositol 3-Kinase/Akt Signaling after Burn Injury

Abstract: Severe burn injury is associated with induction of the hepatic endoplasmic reticulum (ER) stress response. ER stress leads to activation of c-Jun N-terminal kinase (JNK), suppression of insulin receptor signaling via phosphorylation of insulin receptor substrate 1 and subsequent insulin resistance. Marked and sustained increases in catecholamines are prominent after a burn. Here, we show that administration of propranolol, a nonselective β1/2 adrenergic receptor antagonist, attenuates ER stress and JNK activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…(99) In addition, β-blocker treatment resulted in enhanced wound healing at the macroscopic level, and at the microscopic level there was improved epithelialization, collagen deposition, and angiogenesis, as well as decreased protease activity. (100) β-blocker treatment also conferred wound healing advantages in the absence of comorbid metabolic dysfunction.…”
Section: Burns and Wound Healingmentioning
confidence: 99%
“…(99) In addition, β-blocker treatment resulted in enhanced wound healing at the macroscopic level, and at the microscopic level there was improved epithelialization, collagen deposition, and angiogenesis, as well as decreased protease activity. (100) β-blocker treatment also conferred wound healing advantages in the absence of comorbid metabolic dysfunction.…”
Section: Burns and Wound Healingmentioning
confidence: 99%
“…In animal models of cardiomyopathy, norepinephrine administration has been shown to increase ER stress markers and inhibition of ER stress with chemical chaperones has been correlated with decreased norepinephrine levels [54], [55] and [56]. Substantiating evidence for the involvement of catecholamines in ER stress is β-adrenergic receptor blockade effects; treatment with a variety of β-blockers, including both selective and non-selective blockers successfully attenuated ER stress in an array of metabolic conditions while β-agonists produced the opposite effect [57], [58], [59] and [60]. β-blockers have also been shown to modulate levels of Ca-related proteins in ER stress models and norepinephrine specifically has been shown to alter the glycosylation of its transporter (NET), further enhancing the effects of the catecholamine [54] and [59].…”
Section: Organellar Contribution To Hypermetabolismmentioning
confidence: 99%
“…Inhibition of β-adrenergic signalling following thermal injuries has been shown to decrease the cardiac workload, supraphysiological thermogenesis, peripheral lipolysis and ultimately, REE [177]. This β-blocker has also been shown to reduce ER stress, subsequently improving insulin sensitivity [183]. Work by Herndon et al has demonstrated in severely burned (>40% TBSA) children that propranolol treatment increases the net muscle-protein balance by 82% over base-line values, while it decreases by 27% in the control group.…”
Section: Treatment Options To Alleviate the Hypermetabolic Responsementioning
confidence: 99%
“…In addition to the physiological effect of adrenaline on liver glycogenolysis [27], animal studies show that catacholamines directly induce endoplasmic reticulum (ER) stress in hepatocytes [30,31] leading to JNK-dependent inhibition of the phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) pathway after burn [32], thereby promoting insulin resistance [33]. The subsequent hyperglycemia is associated with increased mortality and infectious complications in pediatric burn patients [34] and a prospective analysis of 152 burn patients demonstrated found decreased rates of pneumonia, ventilator-associated pneumonia, and urinary tract infection infections with tight glycemic control [35].…”
Section: Extrahepatic Mechanismsmentioning
confidence: 99%
“…Propranolol works in a dose-dependent manner, with administration ranging from 1–4 mg/kg/day within 10 days to reduce myocardial oxygen requirements and heart rate by 10–20%, without affecting oxygen delivery or resting energy expenditure [131,132,133,134]. Propranolol administration in hyperglycemic burn patients reduces total insulin requirements and attenuates ER stress [32,133]. Propranolol has also been shown to inhibit mobilization of free fatty acids from adipose tissue via β2 adrenergic receptors, while concurrently increasing the efficiency of hepatic fatty acid excretion, resulting in decreased steatosis [135,136,137].…”
Section: Clinical Managementmentioning
confidence: 99%